Price fairness, guest emotions, satisfaction and behavioral intentions in peer to peer accommodation sector - Ali, Laiba; Wong, Foong Yee; Ng, Siew Imm; Akhtar, Muhammad Saood (Scholar Commons, 2018)
The aim of this study is to examine the impact of price fairness on guest emotions, satisfaction and behavioral intentions in Malaysian P2P accommodation sector. The higher level of tourist arrivals towards P2P accommodations sector has drawn the attention of scholars and government. Therefore, this conceptual paper on P2P accommodation proposes an opportunity to examine the influence of external and internal stimuli on guest’s behavioral intentions during their stay in P2P accommodation at Malaysia. The conceptual framework of this study is built on the basis of Stimulus Organism Response (S-O-R) theory. A complete study followed by a conceptual framework will be carried out by using structural equation modeling (SEM). The results of this study will benefit international tourists and local people of Malaysia who are engaged in P2P accommodation sector. In addition, the findings will give a better understanding of S-O-R theory.